Comparison of hypoglycemic effects of ripened pu-erh tea and raw pu-erh tea in streptozotocin-induced diabetic rats. Issue 6 (23rd January 2019) - Ding, Qianzhi; Zheng, Wei; Zhang, Bowei; Chen, Xiaojuan; Zhang, Jie; Pang, Xu; Zhang, Yong; Jia, Dexian; Pei, Surui; Dong, Yuesheng; Ma, Baiping
Abstract : Ripened Pu-erh tea showed stronger anti-diabetic effect than raw Pu-erh tea and showed probiotic role to some beneficial gut bacteria. Abstract : Pu-erh tea is produced from the leaves of large-leaf tea species ( Camellia sinensis var. assamica) in the Yunnan province of China and divided into ripened pu-erh tea (RIPT, with pile-fermentation) and raw pu-erh tea (RAPT) according to processing methods. RIPT extract showed more potent anti-diabetic effects on two-hour postprandial blood glucose (2h-PBG) and fasting blood glucose (FBG) than RAPT extract. UHPLC-Q-TOF/MS and UHPLC-PDA analyses found that 17 newly formed components and the increased components after fermentation, such as quinic acid, gallic acid, caffeine, puerin I and so on, might be the main contributors to the enhanced activities of RIPT. In addition, the probiotic role of RIPT to some beneficial gut bacteria, such as lactobacillus, Prevotellaceae NK3B31 group, Alloprevotella and Prevotella, was observed in our study. These results might provide a clue to anti-diabetic mechanism and active components of pu-erh tea, and use as a functional beverage worth to be further studied.